Lanthanide-containing reversed micelles: A structural and luminescence study - Beeby, A; Clarkson, I; Eastoe, J; Faulkner, S; Warne, B (1997)
Lanthanide surfactants of the type Ln(AOT)3 have been prepared and characterized, where Ln = Tb, Eu, Nd, and AOT is bis(2-ethylhexyl) sulfosuccinate. Small-angle neutron scattering experiments indicate that spherical reverse micelles form in cyclohexane. The luminescence lifetimes of lanthanide ions held inside these aggregates were found to depend on the molar ratio w = [water]/[AOT-]. This behavior is consistent with changes in the Ln3+ solvation: in "dry" micelles the ions are complexed by the surfactant polar groups, while addition of water results in progressive Ln ion hydration. The results show that reversed micelles can be used to control photophysical properties of lanthanides.